Efek Fatigue terhadap Respon Time Penanganan Penderita Gawat Darurat Kategori Australasian Triage Scale 1-5 Versi Indonesia - Nur Intan Hayati Husnul Khotimah; Raden Siti Jundiah; Rizky Muliani; Sriwulan Megawati (Faletehan Health Journal, 2022)
Response time is the indicator of emergency patient management. The handling delay can be fatal, which one of the factors is a high workload causing fatigue. Fatigue was physically characterized by a decrease of movement reflex quality which results on a decrease of emergency response time. This study aimed to identify the effects of fatigue on the response time of emergency patient management. The research design was correlation with cross-sectional approach on 21 emergency department officers who were selected by total sampling technique. The instrument of fatigue measurement was the Indonesian version of Fatigue Severity Scal; while the response time was measured by an observation sheet and stopwatch. The results showed that 52.4% of respondents experienced mild fatigue, 100% response time of emergency patient management was suited to Australasian Triage Scale (ATS) category 1,2,3,4,5 with a median score of 57 seconds, and the response time of 52.4% respondents was less than 57 seconds. The value of Spearman Rank test obtained r value 0.121 which indicates statistically no correlation between fatigue and response time. The weak statistical test results still showed a value that fatigue cause the decrease of problem-solving analysis ability, reflex and movement quality which results on response time decrease. It is necessary to handle fatigue with stress management, work hours arrangement, and adequate rest time management.